Methods used for concentrating oocysts of Cryptosporidium spp., spores Encephalitozoon spp. and Enterocytozoon spp. and their occurrence in Slovak water samples - Sučik, Monika; Valenčáková, Alexandra (Frontiers in Environmental Science, 2023)
The number of outbreaks of water-borne diseases caused by parasites seems to have increased in recent years. Nevertheless, the occurrence of these pathogens in water generally pays little attention. Waterborne transmission is a major route in the epidemiology of the parasite and therefore poses a serious public health problem. Cryptosporidium spp., Encephalitozoon spp. and Enterocytozoon spp. parasites are recognised worldwide as a common cause of diarrhoea. In most cases, it is a dilapidated or poorly maintained standard sanitation and water supply. It is important to perform periodic tests on protozoa, which are often lacking in small laboratories. Since it is necessary to filter large volumes of water for reliable diagnostics and consequently, it is difficult to concentrate them in a large volume of filtrate, it is not easy to detect their presence in the water. Various filtration methods are used to filter these pathogens from water, but cryptosporidial oocysts and microsporidia spores still occur in most of the world’s and Slovak recreational waters. Therefore, it would be appropriate to use the abilities of gill-breathing aquatic animals that filter cryptosporidial oocysts and microsporidia spores from the water by absorbing them with food. Zeolite can also purify water by capturing high concentrations of contaminants, including cryptosporidial oocysts and microsporidial spores.